Implementasi Prinsip Sekolahnya Manusia Dalam Pembentukan Karakter Calon Guru Sekolah Dasar - Faisal Sadam Murron Faisal; Dadang Sundawa; Intan Budi Komara (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2026)
Teacher education at teacher training institutions is at a crossroads between the demands of technical professionalism and the crisis of dehumanization. This study aims to explore how the implementation of Munif Chatib's “Sekolahnya Manusia” (School of Humans) principle, translated as humanistic pedagogy, can shape the civic character of prospective elementary school teachers. This study uses mixed methods with an explanatory sequential design on 40 PGSD students who took the Citizenship Literacy course for eight meetings. Quantitative data (perception surveys) were collected first, followed by qualitative data collection using open-ended questionnaires, in-depth interviews, and observations to explain the quantitative findings. Descriptive quantitative and thematic qualitative data analysis showed that humanistic pedagogy, manifested through (1) the creation of a safe dialogical space, (2) autonomy-based task differentiation, and (3) contextual authentic assessment, contributed significantly to character development. The main findings of this study indicate that the application of humanistic pedagogy through safe dialogic spaces, autonomy-based task differentiation, and authentic assessment contributes to the development of prospective teachers' civic character. Increased empathy and responsibility emerged as the main character values that developed, reinforcing the importance of “humanizing” lectures in shaping prospective teachers who are well-rounded in terms of humanity